Neurophysiological effects of citalopram in a rodent model of ACTH-induced HPA axis dysregulation - Lubbe, Andréa (University of the Witwatersrand, Johannesburg, 2024)
Background. Major depressive disorder (MDD) is a debilitating disorder that affects approximately 300 million people worldwide. Despite multiple theories being implicated in the pathogenesis of MDD, most antidepressant drugs primarily target the monoaminergic theory of depression. Selective serotonin reuptake inhibitors (SSRIs) form a part of the most prescribed antidepressants that target the monoaminergic system. Following treatment with antidepressants, around 30% of patients with MDD continue to experience depressive symptoms, rendering them treatment resistant. The most widely accepted definition of treatment resistant depression is the resistance to at least two antidepressant regimens following the proper dose for an adequate amount of time. Treatment resistance in MDD has been attributed to dysregulation of the hypothalamic-pituitary-adrenal (HPA). HPA axis dysregulation leads to chronically high levels of glucocorticoids and failure of the regulatory negative feedback system. Consequently, there is a need for the development of novel drugs and validated animal models to study the antidepressive mechanism of these drugs. The aim of this study was to validate a rodent model of depression via chronic administration of adrenocorticotropic hormone (ACTH), and to investigate the effects of citalopram (a SSRI) on depressive-like symptoms using neurobehavioural tests and the regional brain expression of molecular markers associated with depression. Methods. Thirty-nine Sprague-Dawley rats (n=20 female; n=19 male) were randomly divided into a control group (n = 10 female, n= 9 male) and a depressed group (n=10 female; n=10 male). Rats in the control group received daily subcutaneous injections of saline (100μg/day) for two weeks. The depressed group received ACTH (100μg/day) subcutaneously daily for two weeks. Following the 2-week administration of ACTH or saline, all animals received citalopram (10mg/kg bw) for four weeks intraperitoneally, concurrently with ACTH or saline. The open-field test was performed to determine anxiety-like behaviour by assessing locomotor activity and time spent in central versus peripheral zones. The OFT was performed prior to the initiation of ACTH or saline administration. Following the 2-week administration of ACTH, the OFT was performed again to determine the effects of ACTH. The OFT was performed for a final time following citalopram treatment. The sucrose preference test (SPT) was performed to determine the presence of anhedonia. During the test, the rats were placed in the SPT apparatus with two water bottles for 12 hours. Water bottles were weighed before and after the test. After the four weeks of drug administration, rats were terminated by decapitation using a rodent guillotine. Brains were surgically removed, and the prefrontal cortex, striatum, hippocampus, and midbrain were surgically dissected and frozen. The RNA was isolated, and cDNA synthesised. Molecular gene expression analysis was performed for BDNF, CREB, TrkB, Akt, mTOR, and eEF2 using real-time polymerase chain reaction. Results. During the OFT, immobility increased in male and female saline + citalopram and ACTH + citalopram rats after 6 weeks (all p<0.05). During the SPT, females that received ACTH + citalopram had a higher preference for regular water consumption (p=0.004). In males, sucrose preference ratio was lower in ACTH + citalopram males than in saline + citalopram males (p=0.007). Regional mRNA expression of BDNF was significantly different between males and females (p<0.003). In the striatum, ACTH + citalopram females had higher expression of BDNF compared to ACTH + citalopram males (p=0.007). In the midbrain, ACTH +citalopram males had higher expression of BDNF compared to ACTH + citalopram females (p=0.01). Regional expression of mRNA of CREB resulted in a sex (p<0.0001) and treatment effect in the prefrontal cortex and midbrain (p<0.05). In the prefrontal cortex and midbrain, saline + citalopram and ACTH + citalopram males had higher mRNA expression of CREB than females (all p<0.001). There was a sex effect in the TrkB mRNA expression in the prefrontal cortex (p=0.005), as ACTH + citalopram females had a higher mRNA expression than ACTH + citalopram males (p=0.02). In the striatum, ACTH administration led to a higher TrkB mRNA expression in females compared to males (p=0.04). No significant differences were observed in mTOR mRNA expression between any of the groups (all p>0.05). In the midbrain, ACTH + citalopram females had a lower eEF2 mRNA expression than ACTH + citalopram males (p=0.02). Conclusion. This study suggest that male animals may exhibit greater susceptibility to neurobehavioural effects of ACTH, as oestrogen in females may be protective in regulating HPA axis function. Neurobehavioural changes in male rats may be linked to ACTH-induced effects on the dopamine system, affecting locomotor activity and reward processing. These results aid our understanding of the pathophysiology of depression related to HPA axis dysregulation. Nevertheless, the effects of ACTH induced dysregulation of the HPA axis on monoamine signalling, neuroinflammation, and GABA/glutamate neurotransmission, warrant further investigation
A dissertation submitted in fulfillment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Physiology University of the Witwatersrand, Johannesburg, June 2024
Keywords: depression; ACTH; HPA axis; SSRI; UCTD; SDG-3: Good health and well-being